PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI PADA MATERI SISTEM PENCERNAAN DI SMP - Khalida Ulfa; Lia Rozalina (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
This research was aims to developed, feasibility and compare differences in learning out-comes before and after used Monopoly Games Smart (MGS) learning media on digestive system topic in junior high school IBA Palembang. Research applies Research and Development methods with steps, namely define, design, and development. Egibility was based on the evaluation of media expert and small scale trials. Data collection in this study used interviews, questionnaire and documentation. Analysis tehcnique were including analysis of product data.. The results show that the Monopoly Games Smart (MGS) learning media has significant effect in improving the mastery of concept. Based on students mastery of concept showed that the implementation of learning using Monopoly Games Smart (MGS) is better than convensional. The learning process in the digestive system topic is more effective and student centered which makes students more active in learning and makes the learning process more meaningful. If the learning response is good, mastery of the concept will be good.